Incidence of interruptive penicillin allergy alerts in patients with previously documented beta-lactam exposure: Potential for leveraging the electronic health record to identify erroneous allergies. (13th September 2022) - Van Groningen, Nicole; Duncan, Ray; Cook-Wiens, Galen; Kwong, Aaron; Sonesen, Matthew; Nuckols, Teryl K.; Cassel, Suzanne L.; Pevnick, Joshua M.
Abstract: Background: Approximately 10% of patients report allergies to penicillin, yet >90% of these allergies are not clinically significant. Patients reporting penicillin allergies are often treated with second-line, non–β-lactam antibiotics that are typically broader spectrum and more toxic. Orders for β-lactam antibiotics for these patients trigger interruptive alerts, even when there is electronic health record (EHR) data indicating prior β-lactam exposure. Objective: To describe the rate that interruptive penicillin allergy alerts display for patients who have previously had a β-lactam exposure. Design: Retrospective EHR review from January 2013 through June 2018. Setting: A nonprofit health system including 1 large tertiary-care medical center, a smaller associated hospital, 2 emergency departments, and ˜250 outpatient clinics. Participants: All patients with EHR-documented of penicillin allergies. Methods: We examined interruptive penicillin allergy alerts and identified the number and percentage of alerts that display for patients with a prior administration of a penicillin class or other β-lactam antibiotic. Results: Of 115, 081 allergy alerts that displayed during the study period, 8% were displayed for patients who had an inpatient administration of a penicillin antibiotic after the allergy was noted, and 49% were displayed for patients with a prior inpatient administration of any β-lactam. Conclusions: Many interruptive penicillin allergy alerts display for patients who would likely tolerate a penicillin, and half of all alerts display for patients who would likely tolerate another β-lactam.